Dermatological manifestations of polycystic ovary syndrome: A literature review (International Seven Journal of Multidisciplinary, 2024)
Objective: To identify and understand the pathophysiology of dermatological clinical manifestations in patients with Polycystic Ovary Syndrome. Literature review: Polycystic ovary syndrome (PCOS) is highly common among women of reproductive age. Although its etiology is poorly understood, the diagnosis is made by associating the various clinical manifestations of the disease and using the Rotterdam criteria - at least two of which are hyperandrogenism, multiple ovarian cysts and irregularity of the menstrual cycle. The symptoms are divided into dermatological, systemic, gynecological and reproductive. Dermatological symptoms include hirsutism, acne vulgaris, acanthosis nigricans, seborrheic dermatitis, androgenetic alopecia and, in more severe cases, virilization. Patients with PCOS often have a reduced quality of life due to its complications, including difficulty getting pregnant, gestational complications and even infertility. For the best management of this syndrome, a multidisciplinary approach is needed, involving various areas of medicine in line with the patient's complaints, and a clinical control approach for circulating androgen levels.